PENGARUH PENETRASI INTERNET TERHADAP TINGKAT KEMISKINAN DI INDONESIA ANALISIS DATA PANEL PROVINSI TAHUN 2015–2024 - Aulia, Salwa; Aulia Lestari Ramadhani; Naila Farah; Deandra Ayesha Manayra; Naufal Rafi Fajar; Fitri Amalia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of digitalization in Indonesia has not been fully accompanied by a reduction in poverty levels across regions. This study aims to analyze the effect of internet penetration on poverty levels in Indonesia using a panel data regression approach. The study employs secondary data obtained from the Central Statistics Agency (BPS), covering 34 provinces in Indonesia during the period 2015–2024, resulting in a total of 340 observations. The dependent variable in this study is the poverty rate, while the independent variables include internet penetration, mean years of schooling, Gross Regional Domestic Product (GRDP), and the open unemployment rate. Model selection was conducted using the Hausman test, which indicated that the Random Effect Model (REM) was the most appropriate estimation method. In addition, robust standard errors were applied to address heteroscedasticity problems and to produce more valid and reliable estimates. The results show that, partially, internet penetration and the open unemployment rate do not have a significant effect on poverty levels, whereas mean years of schooling and GRDP significantly contribute to poverty reduction in Indonesia. These findings indicate that increased internet access has not been fully accompanied by productive and equitable digital utilization across regions. Meanwhile, improvements in educational quality and regional economic growth have proven to contribute to poverty reduction. Therefore, poverty alleviation efforts require integrated policies through improving educational quality, promoting equitable economic development, and strengthening digital literacy and digital infrastructure in order to encourage a more inclusive utilization of digital transformation.